Organisational culture, values and performance in multinational companies in Mauritius - Ramhit, Ketan Sharma (University of the Witwatersrand, Johannesburg, 2022)
The national identity of Mauritius is built on its distinctive culture, history, and beliefs, which inform how people see the world. Multinational companies (MNCs) have beenattracted to Mauritius due to its role as an economic hub and proximity to African continental markets. In a globalised context, organisations increasingly need to understand what drives employee behaviour and the relationships between the individual values of their staff and their individual performance. This study investigates how individual values affect Mauritius Multinational Companies (MNCs) employee performance. It draws from the Global Leadership and Organisational Behaviour Effectiveness (GLOBE) organisational culture theory as well as Hofstede’s cultural values theory to understand relationships between organisational cultural values and employee performance. While Schwartz's theory acknowledges the influence of biological needs and social contexts on an individual's value priorities, it presents a more comprehensive approach byemphasising the psychological aspect of values. His theory recognises that an individual's biological needs and social environment can significantly impact their value system and subsequent choices. First, a modified grounded theory methodology was used in Stage 1 to conduct in-depth interviews with MNC managers utilising census sampling. Data analysis employed theoretical coding and constant mapping to derive a theoretical model of the relationships between individual values and individual performance. Through a process of exploring and explaining data, the theoretical framework emerged. Once the theoretical propositions were established, a model was derived from them and further strengthened by the relevant literature. Once the initial codes were established in the first step of qualitative analysis, the second step involved connecting these codes to concepts and themes. The step was accomplished by utilising a modified version of the Gioia approach. The Gioia approach employs a schematic representation to assess qualitative data and construct a visual data structure. A comprehensive theoretical model was constructed by deriving theoretical propositions and supplementing them with relevant literature. The values that emerged from the qualitative study aligned with Schwartz's value dimensions. In Stage 2, a quantitative ii survey was used to gather information from MNCs. Schwartz’s values dimensions were tested as to their relationships with employee performance. The model was tested using confirmatory factor analysis and structural equation modelling. Schwartz's higher-order values were found to significantly predict individual performance. These, together with work attitudes, motivation, and the work environment were found to be significant predictors of individual performance. Theory predicting moderating relationships of age, gender, and educational attainment on the relationships between individual values and individual performance was also tested, but no evidence of their moderating effects was found. Two models were assessed - one individual performance as the dependent variable, while the other used intention-to-quit. The model using individual performance displayed acceptable fit indices, but the one using intention-to-quit did not satisfy the requirements for model fit. In conclusion, this study highlights the critical role that individual values play in determining individual performance inside Mauritius MNCs, offering insightful information for businesses doing business there
A Thesis Submitted in Fulfilment of the Requirements for the Degree of Doctor of Philosophy (Ph.D. Management), School of Business Sciences, Faculty of Commerce, Law and Management, University of the Witwatersrand, 2022
Keywords: Multinational companies (MNCs); Economic hub; Individual performance; Mauritius Multinational Companies (MNCs); Organisational Behaviour Effectiveness (GLOBE); UCTD; SDG-8: Decent work and economic growth